Experimental analysis of peer-to-peer streaming in cellular networks - Díaz-Zayas, Almudena; Merino-Gómez, Pedro; Panizo-Jaime, Laura; Recio, Álvaro M. (IEEE, 2007)
In this paper, we study the adequacy of applying peer-to- peer techniques to mobile networks by conducting a series of experiments using smart phones as peers. We measure important parameters, such as jitter and packet losses, in static and dynamic scenarios, focusing on a video streaming service. Finally, based on the results obtained, we discuss the feasibility of these applications.
10.1109/AINA.2007.67
Keywords: Sistemas de comunicaciones móviles; Streaming media; QoE evaluation; QoS evaluation; cellular networks